An unusual palatal mass in a 54-year-old male: report of a rare case - Srinivasan Ranjanee; Kumar Mathangi; Vineetha Ravindranath; Nayak Dipak Ranjan; Sharma Swati (EDP Sciences, 2022)
Rhinosporidiosis is a chronic, granulomatous, muco-cutaneous infection caused by Rhinosporidium seeberi. The infection is non-contagious and sporadic in humans, affecting predominantly the mucous membrane of the upper respiratory tract. It is quite an uncommon condition and seldom affects the oral mucosa. The clinical presentation of this condition in the oral cavity can mimic many other conditions. Here, we report a unique case of recurrent rhinosporidiosis affecting the palate in a 54-year-old male.